DINAMIKA KOALISI POLITIK DI BALIK DEMOKRASI KEINDONESIAAN: OPOSISI MENJADI ANCAMAN? - Sagala, Christo Sumurung Tua (Veritas et Justitia, 2025)
In a democratic system, opposition plays a vital role in providing checks and ensuring that the government operates in alignment with the public interest. However, within the context of Indonesia, opposition is often viewed as a taboo, seen as conflicting with the values of Pancasila and the familial principles that define Indonesian society. This article explores the historical development of opposition in Indonesian democracy and the role of checks and balances within the framework of the trias politica, as part of the broader effort to advance democratization in Indonesia. Employing a socio-legal approach, the study examines Indonesian democracy from theoretical, historical, and practical perspectives. It concludes that the evolution of Indonesian democracy cannot be separated from the post-independence ideological debate between proponents of integralism and those advocating for social democracy. This debate ultimately gave rise to the concept of a “family state,” where the state acts as a father figure and the citizens as children. The Reformasi era marked a transitional phase toward democratization, introducing constitutional liberalism alongside the principles of checks and balances and the trias politica. However, these democratic instruments have not been effectively implemented. Indonesia remains entangled in political party cartelization, reinforced by a system of coalition presidentialism and supported by Constitutional Court decisions that emphasize strengthening the presidential system and simplifying the party structure. As a result, political parties in the legislature tend to focus more on positioning themselves for the next presidential election and securing roles within the governing coalition, rather than engaging in meaningful oversight of government actions.